Runs, transparency and regulation: On the optimal design of stablecoin frameworks - Olli Castrén; Riccardo Russo (European Banking Authority (EBA), 2024)
Stablecoin issuers can become subject to runs just like banks. This is because, in the absence of adequate regulation, issuers are incentivised to hold disproportionate amounts of high-yielding but illiquid assets in their reserve portfolios. The value of such reserve assets may be overly volatile, thus inducing investors to suddenly redeem their stablecoins. To mitigate the risk of runs, recent regulatory initiatives propose that reserve-asset portfolios should be overcollateralized, and that stablecoin issuers provide sufficient disclosure to holders about their composition. We show how transparency incentivises stablecoin issuers to keep a larger share of the reserves in liquid assets, thus reducing the risk of runs and potential bankruptcy ex-ante. In addition, transparency on reserves disincentivises stablecoin holders from irrationally demanding the reimbursement of their funds. We calculate the social welfare under different equilibria and analyse how regulatory interventions, like suspension of redemptions, may affect the welfare outcomes.
Keywords: G23; G28; I30; 330; Stablecoins; Runs; Transparency; Regulatory Policy; financial transparency; virtual currency; financial risk